Cognitive Training Using Virtual Reality: An Assessment of Usability and Adverse Effects - Myeonghwan Bang, MD; Min A. Kim, BS; Sung Shin Kim, BS; Hyoung Seop Kim, MD, PhD (Archives of Rehabilitation Research and Clinical Translation)
Objective: To evaluate the usability and adverse effects associated with virtual reality (VR) cognitive training and identify factors influencing them. Design: Survey-based observational study. Setting: Department of Rehabilitation Medicine in the hospital. Participants: Twenty rehabilitation professionals (mean [standard deviation] age; 30.0[4.8] years, men 8[40%], and women 12[60%]) and 10 patients with stroke (mean [SD] age; 64.1[13.6] years, men 2[20%] and women 8[80%]). Interventions: The participants wore a head-mounted display (Meta Quest2) and consecutively underwent 5 custom-designed cognitive training. Main Outcome Measures: After the training, participants completed 3 questionnaires: the systemic usability scale, user experience questionnaire (UEQ), and cybersickness in VR questionnaire. Results: The mean systemic usability scale score was 55.1 and 52.3 for rehabilitation professionals and patients, respectively. For the UEQ, the mean score for each item, including attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty, were 0.9/0.2, 0.6/0.2, 0.5/−0.5, 1.2/0.8, 0.9/0.4, and 0.6/0.8 for rehabilitation professionals/patients, respectively. Rehabilitation professionals had slightly higher scores in most UEQ items. The mean cybersickness in VR questionnaire scores were 18.6 and 19.0 for rehabilitation professionals and patients, respectively. Conclusions: Participants reported moderate usability and a generally below-average user experience, with mild-to-moderate VR sickness during VR cognitive training. The rehabilitation professionals rated usability higher than the patient group, while patients experienced more severe VR sickness. These findings may serve as a significant insight for developing VR cognitive training for application to patients in the future.